PENGEMBANGAN BAHAN AJAR BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) PADA MATA PELAJARAN IPS UNTUK MENINGKATKAN KARAKTER CINTA LINGKUNGAN HIDUP SISWA DI SMP NAZATUT THULLAB SAMPANG MADURA - Dularip . (Jurnal Education and Development, 2020)
This research tries to develop social studies teaching materials based on Education for sustainable development (ESD) at SMP Nazatut Thullab Prajjan Sampang. In this case, the researcher tries to present the concept of Education for sustainable development (ESD) in the social studies subject in relation to the interaction of humans with their environment, which is carried out on class VIIB students at Junior high school\ Nazhatut Thullab Prajjan Sampang. The purpose of this research is how to provide an alternative for the development of social studies teaching materials that are able to develop students' caring attitude towards the surrounding environment. The research uses quantitative research methods, the type of research R & D from Borg and Gall. The results showed that books or social studies teaching materials based on Education For Sustainable Development (ESD) were able to respond to students in developing a character of love for the environment. This is also based on the results of the calculation of t count 14.210 greater than t table. 2,0322 So Ho is rejected and Ha is accepted, so that there is a significant difference between student scores before and after using the Education For Sustainable Development (ESD) based social Scienceslearning module.